Public relations writing strategies & structures - Newsom, Doug.; Haynes, Jim. (Boston, MA Cengage Learning, 2017)
Combining the practical approach of a trade book with fundamental PR principles and theories, PUBLIC RELATIONS WRITING: STRATEGIES & STRUCTURES, 11th Edition, thoroughly equips students with the essential techniques and methods needed to write with understanding and purpose. The Eleventh Edition takes a more strategic focus as it guides students through a logical progression of PR writing, starting with the roles and responsibilities of the PR writer, followed by writing principles, preparing to write, writing for select audiences, and writing for turbulent times. It also introduces different styles and techniques behind writing principles. In addition, the text now includes an entire chapter devoted to writing for social media.
Prof. Ma. Theresa Tabada (Recommending faculty) - Bookfair2017
Keywords: Public relations; Public relations|xAuthorship.; Business writing